ANALISISMODEL ANTRIANPADA PELAYANAN PELANGGAN (STUDI KASUS PENGISIAN BAHAN BAKAR PADA SPBU KOTA JAMBI) - Ahmad Firdaus (J-MAS (Jurnal Manajemen dan Sains), 2016)
The study entitled analysis of queueing model on customer service, the object on the study is Gas Stations 24.361.35 city of Jambi. The purpose of this research is tolook at the situation which occurred in Gas Station queues 24.361.35 city of Jambi, the source of the data in this study is primary data obtained from direct observations in the field, and the secondary data in the form of books relating to the research, while the processing of data in this study using POM/QM software for Windows 3.0. from the results of the data processing can be drawn the conclusion that the model applied by Gas Station queues 24.361.35 Jambi City can be said to be optimal, this is because the number of customers who come in can be served well with a short queue time.Keywords : queue, service, customer